2016
DOI: 10.1021/acsenergylett.6b00328
|View full text |Cite
|
Sign up to set email alerts
|

Implications of 4 e Oxygen Reduction via Iodide Redox Mediation in Li–O2 Batteries

Abstract: Li-O 2 cells with slight variations in design and material were employed in three different laboratories for this work, but all show consistent results. Figures 2, 3 and 6 were performed in one lab, Figure 1, 5, 7 and 8 in another, and Figure 4 in a third, but key experiments were repeated in all labs to confirm consistency. In order to provide specific repeatability, we will discuss specific cell materials, cathode preparation, and cell assembly pertaining to the data from Figures 2, 3 and 6. Materials.Lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
207
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(232 citation statements)
references
References 41 publications
14
207
4
2
Order By: Relevance
“…25 If this decomposition mechanism results in oxygen evolution, it would make a new reversible mechanism for the Li–O 2 battery, which is currently under debate as it has been proposed to be thermodynamically unfavorable 26 and it has been suggested that I – is oxidized rather than LiOH. 27 Burke et al 28 have recently reported that the LiOH crystallite was formed by a four-electron reduction process with the addition of LiI and H 2 O in the DME electrolyte upon discharge; however, the decomposition of the LiOH crystallite was primarily attributed to iodo–oxygen electrochemistry rather than reversible oxygen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…25 If this decomposition mechanism results in oxygen evolution, it would make a new reversible mechanism for the Li–O 2 battery, which is currently under debate as it has been proposed to be thermodynamically unfavorable 26 and it has been suggested that I – is oxidized rather than LiOH. 27 Burke et al 28 have recently reported that the LiOH crystallite was formed by a four-electron reduction process with the addition of LiI and H 2 O in the DME electrolyte upon discharge; however, the decomposition of the LiOH crystallite was primarily attributed to iodo–oxygen electrochemistry rather than reversible oxygen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, some mediators such as LiI and LiBr have recently been applied to glymebased electrolytes to promote Li 2 O 2 oxidation at the air electrode. [13][14][15][16] Meanwhile, to suppress Li dendrite growth at the Li metal negative electrode (NE), a new inorganic Li salt, i.e., LiNO 3 , has been applied to glyme-based electrolytes to stabilize the surface by oxidation.…”
mentioning
confidence: 99%
“…In addition, sustainable charge redox mediators could accelerate the decomposition of insulating products by moving into the cathode electrode and facilitating the transport of electrons between the insulating products and the cathode electrode during charging. Many charge redox mediators have been reported, such as lithium iodide (LiI), [151,152] lithium bromide (LiBr), [148,153] tetrathiafulvalene (TTF), [82] tris [4-(diethylamino)phenyl]amine (TDPA), [154] 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), [155,156] phthalocyanine (FePc), [157] and heme molecules. [158] Taking the iodide (I -) ion as an example, it could be oxidized to I 3 − or I 2 on the surface of the electrode during charging and then react with Li 2 O 2 to form Li + and O 2 gas with the regeneration of I − ions.…”
Section: Charge Redox Mediatormentioning
confidence: 99%